Efeito de bioestimulador do solo e adubação mineral sobre atributos edáficos e produtividade de culturas anuais - Zanellato, Daiane Cristina (2018)
In the search for more efficient ways to manage soil fertility, agricultural inputs have appeared on the market claiming to present technical and agronomic characteristics that result in benefits to biological, physical and chemical properties of soils. However, the mechanisms of operation of these inputs are not fully understood. In this sense, the objective of this work was to evaluate the use of Microgeo [Marca Registrada] soil biostimulator associated with mineral fertilization with nitrogen (N), phosphorus (P) and potassium (K) in annual crops. The experiment was implemented in May 2015 at the Universidade Tecnológica Federal do Paraná, campus Dois Vizinhos (UTFPRDV). The experimental design was randomized blocks with four replicates. The treatments used consisted of doses of the biostimulator associated with soluble mineral fertilizer with NPK according to nutrient content in the soil and thus defined: treatment T0 = 0% of biostimulator and 0% of NPK; T1 = 100% biostimulator and 0% NPK; T2 = 0% biostimulator and 100% NPK; T3 = 50% biostimulator and 100% NPK; T4 = 100% biostimulator and 100% NPK; and T5 = 150% biostimulator and 100% NPK. The evaluated crops were soybean (2015/2016) beans (2016) and maize (2016/2017), being analyzed the microbiological and chemical parameters in the soil, nutrient content in the plant tissue of the crops and the yield of the same. The analysis of variance (ANOVA) was performed and, when significant, the Scott Knott test was used, at 5% probability. It is concluded that the use of the soil biostimulator in this work and its conditions did not influence the microbiological and chemical parameters of the soil and the productivity of the annual crops. Mineral fertilization is essential for the maintenance of yield of annual crops even in soils with adequate availability of P, K and high levels of organic matter.